Analisis Efektifitas Penggunaan Metode Soft Starter saat Start awal pada pengoperasian Motor 220 kW - Andi Junaidi; Susan Damayanti (Sekolah Tinggi Teknik PLN, 2019)
The Multipurpose Reactor G.A Siwabessy is a research reactor equipped with a Cooling System consisting of 2 systems, namely the primary cooling system and the secondary cooling system. This Project discusses the effectiveness of using the Soft starter method in the initial starting process of the electric motor in the secondary cooling system which aims to reduce the value of a high current surge when the motor starts working. The data type used is primary data obtained directly by the author through a measurement process with a measuring instrument. When using the Star-Delta method the surge current is 765 A while with the Soft starter method there is a decrease in the current surge value to 517 A, the conclusion of the result is a decrease in the current surge value of 0,677% using the Soft starter method .